FurA-Dependent Microcystin Synthesis under Copper Stress in Microcystis aeruginosa - Yuanyuan Chen; Jiaojiao Yin; Jin Wei; Xuezhen Zhang (Microorganisms, 2020)
Massive blooms of cyanobacteria frequently occur with microcystin (MC) production. Cyanobacteria are exposed to copper stresses such as copper algaecides which are often used to remove cyanobacterial blooms. However, copper increased the MC production of cyanobacteria, and the underlying mechanism remains unclear. The present study investigated the relationship between copper exposure (0.5 and 3 µM) and MC synthesis in Microcystis aeruginosa PCC 7806. The study concluded that the content of intracellular MCs increased by nearly two times both in 0.5 and 3 µM copper. High-throughput RNA sequencing (RNA-seq) provided evidence that copper mainly attacked Fe–S clusters, with evidence of changes in iron, sulfur, iron uptake regulators (fur), glutaredoxins and dehydratase genes. The transcription of numbers of genes implicated in iron uptake, MC synthesis and furA was also evaluated with quantitative real-time PCR (qRT-PCR). In these three Cu treatment groups, the amount of MCs increased as copper elevated. As the expression of mcyD gene was directly regulated by FurA and copper ions affected the expression of the FurA-related genes, we believed that MC synthesis genes were controlled by copper. This study has made a further understanding of the mechanism of the increase in MC synthesis of M. aeruginosa PCC 7806 treated with copper-based algaecides. We aimed to understand the mechanism of copper ion influencing the synthesis of MCs.